L’apprentissage de la coopération intercommunale : modalités et instruments - Lilian Loubet (L'Espace Politique, 2012)
The development of the inter-municipal cooperation gives rise to some major territorial and governmental reorganization. The elected in charge are then confronted to the complex exercise of the municipal cooperation and the definition of a territorial project. It will be a question of studying the inter-municipal cooperation towards the technical, political and “territorial learning” operated by the mayors. That is illustrated by the study of the Toulouse city région, which is splited in three metropolitan council of governments : it shows more or less advanced territories in the community integration process. Some technical managers and more than eighty mayors were asked about that.